High effectiveness self-cleaning activity on TiO2/rGO nanocomposite synthesized by mangosteen (Garcinia mangostana L.) peel extract - Maisari Utami; Luthfia Sinta Rahmadhani; Karna Wijaya; Balasubramani Ravindran; Mir Waqas Alam; Latifah Hauli; Aditya Rianjanu; Indra Purnama; Gani Purwiandono; Salmahaminati (Results in Engineering)
The fabrication of TiO2/rGO nanocomposites employing mangosteen peel extract as a bioreductor for self-cleaning applications has been successfully conducted. The research reduced graphene oxide (GO) to rGO using mangosteen peel extract as the reducing agent. TiO2 synthesis was carried out via a biosynthesis method using mangosteen peel extract while TiO2/rGO nanocomposite was obtained using hydrothermal method. TiO2/rGO had an anatase phase with a crystal size of 10.439 nm and band gap energy of 3.04 eV which is lower than TiO2 (3.12 eV). Moreover, TiO2/rGO demonstrated mesoporous characteristics with a high surface area of 95.845 m2/g. TEM morphology revealed TiO2 nanoparticle spheres uniformly dispersed on rGO sheets, with 11.2 nm as the average particle size. The time-dependent density functional theory (TD-DFT) computational method showed the distance between methylene blue (MB) atoms and rGO to be 1.6 Å, with the highest oscillator strength of 0.7801, indicating a HOMO −1→LUMO +1 transition, which experiences excitation from π to π*. Photocatalytic self-cleaning tests of the TiO2/rGO nanocomposite on MB degradation demonstrated that irradiation with visible light produced superior photocatalytic activity compared to dark and UV light conditions, achieving a degradation percentage of 99.20%. The water contact angle of the TiO2/rGO material decreased from 58° before irradiation to 52° after visible light irradiation, indicating the hydrophilic characteristic and effective self-cleaning capabilities of the TiO2/rGO nanocomposite.